2017
DOI: 10.1609/icwsm.v11i1.14907
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Content Quality in Collaborative Knowledge Production

Abstract: We explore the dynamics of user performance in collaborative knowledge production by studying the quality of answers to questions posted on Stack Exchange. We propose four indicators of answer quality: answer length, the number of code lines and hyperlinks to external web content it contains, and whether it is accepted by the asker as the most helpful answer to the question. Analyzing millions of answers posted over the period from 2008 to 2014, we uncover regular short-term and long-term changes in quality. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…This suggests that performance on these platforms has a non-trivial dynamic component that merits deeper investigation. Indeed, a study of Stack Exchange observed short term deterioration in performance (Ferrara et al 2017). Our study suggests that such an effect may be general.…”
Section: Discussionsupporting
confidence: 53%
“…This suggests that performance on these platforms has a non-trivial dynamic component that merits deeper investigation. Indeed, a study of Stack Exchange observed short term deterioration in performance (Ferrara et al 2017). Our study suggests that such an effect may be general.…”
Section: Discussionsupporting
confidence: 53%
“…This observation is consistent with an analysis of 18 interviews by Rieh et al (Rieh et al 2017), where they reported that as a result of providing answers in a CQA environment, users (teens) were able to expand their knowledge bases, improve inquisitiveness, embrace challenging questions, and increase self-confidence. Moreover, a recent study on quality of content in a CQA environment by Ferrara et al (Ferrara et al 2017), revealed a long-term trend in terms of improvement of quality of answers due to learning and skill acquisition by users over time.…”
Section: Questions In Pythonmentioning
confidence: 99%